Business Model Design and Learning - Spencer, Barbara (Business Expert Press, 2013)
Ebook from IG Library ; So many of us have asked ourselves--what's a business model? What's a good business model? This book has all the answers--it explains what a business model is, what you have to do to get one, and what to do about the one you've already got.